CONTRIBUTION TO THE STATISTICAL INTERPRETATION OF RAW MATERIALS FOR THE CEMENT INDUSTRY OF SPLIT - Miroslav Matijaca; Slavko Vujec (Rudarsko-geološko-naftni Zbornik, 1990)
Up to the last two decades cement was produced from mari called »tupina« (with about 76% CaCOj) which is an ideal mixture for cement production. Due to the quantity decrease of this raw material, cement production went on using the mixture of other members of the flysch series: limestones, marls, clay, loess, sandstones a.o. By the analysis of natural materials the CaCO^ content has mostly been proved. Therefore, knowing the correlation of oxides in mineral raw material is of special significance. The article discusses investigation results of the correlation between CaCO-i and other oxides of the raw material (the paper is published in Croatian).